Maternal Serum Biochemical Indicators of Trophoblastic Cell and Endothelial Function at First Trimester of Pregnancy - Ranjeeta Gadde; Chikkanayakanahalli Doddaiah Dayanand; Shimoga Rangappa Sheela (New Frontiers in Medicine and Medical Research Vol. 9, 2021)
Background: Preeclampsia is a worldwide pregnancy complication, and early identification of patients with an increased risk is one of the key goals in obstetrics. The precise origin of preeclampsia remains elusive but the impairment in the early placentation is thought to be associated with the pathogenesis of the disorder. First trimester screening is crucial over the second trimester for understanding the early onset of the disorder, with basal levels of the biochemical parameters associated with the underlying placentation process. Objective: The study aims to assess the levels of serum biochemical markers in pregnant women at first trimester, to evaluate statistical significance and correlation of the values in support of trophoblastic cell integrity, endothelial function and oxidative stress. Materials and Methods: A longitudinal study was conducted on 86 pregnant women of age group 20 - 35 years, Primigravida with singleton pregnancy who visited prenatal check up between 11 - 13 weeks of gestation. Maternal sera was collected for screening Placental protein 13 (PP13), Caspase 3, Asymmetric dimethylarginine (ADMA), Nitric oxide (NO) by ELISA. Xanthine oxidase (XO) activity was assayed spectrophotometrically. Calcium and Uric acid (UA) were measured by dry chemistry analyser. Results: The mean \(±\) SD values for mean arterial pressure (MAP) are 108.4 \(±\) 18.9, UA 2.01 \(±\) 0.85, Total oxidant status (TOS) 12.83 \(±\) 5.17, Total antioxidant capacity (TAC) 24.10 \(±\) 14.28, XO 1.01 \(±\) 2.67, Caspase- 3 1.76 \(±\) 2.22, PP13 489.77 \(±\) 53.6, Calcium 10.88 \(±\) 1.97, ADMA 19.03 \(±\) 17.08 and NO 1.16 \(±\) 0.75. The statistical analysis by SPSS package version 20 revealed positive correlation between ADMA & Caspase-3 (r = + 0.435), PP13 & NO (r = + 0.241), TOS & TAC (r = + 0.176), UA & ADMA (r = + 0.176), UA & TAC (r = + 0.168) and negative correlation between PP13 & ADMA (r = - 0.158), NO & TOS (r = -0.114), UA & XO (r = -0.173), UA & NO (r = -0.186), UA & Caspase 3 (r = -0.106) and MAP & Calcium (r = -0.303). Conclusion: The study concludes that first trimester biochemical markersand their correlation predict the trophoblastic cell integrity and endothelial function during placentation under prevailing oxidative stress conditions, which may help in identifying women who subsequently go on to develop preeclampsia.